Impact of Surfactants on the Performance of Plastic Modified Bitumen: A Study on Ductility, Penetration, and Softening Point - Nugraha Wahyu Pratama; Mochamad Chalid; Farhan Aziz (Jurnal Sains Materi Indonesia, 2025)
This study explores the effect of surfactant use, namely Sorbitan Monostearate (Span 60) and Polyethylene Glycol 400 (PEG 400), on the physical and mechanical characteristics of bitumen modified with multilayer plastic. The focus of this study is to improve the compatibility between bitumen and multilayer plastic, which often have incompatible properties, thus affecting the performance of bitumen. Methodology applied includes the preparation of bitumen samples modified with varying surfactant concentrations, followed by microscopic analysis to assess particle dispersion and distribution. The results showed that the addition of surfactants significantly improved particle dispersion, with smaller particle sizes and more even distribution. Ductility tests showed that bitumen modified with surfactants had better flexibility compared to conventional bitumen, while penetration tests showed improved elasticity properties. These findings indicate that the use of surfactants in bitumen modification can improve the physical and mechanical properties of the material, providing potential for wider applications in the construction industry. Further research is recommended to explore other surfactant combinations and their impact on bitumen properties under various environmental conditions.